Point of care diagnostics for carbonyl/oxidative stress biomarkers - Gopal, Ammanath (2018)
Multiple triggers like exogenous and endogenous factors could affect the equilibrium levels of free radicals and reactive oxygen species in humans. For instance, elevated concentration levels of reactive carbonyl species (carbonyl stress) or reactive oxygen species (oxidative stress) damages a myriad of important biological molecules such as proteins, lipids, carbohydrates and nucleic acids. Damage to these molecules causes cell death and tissue injury, thus contributing to various disorders like type 2 diabetes mellitus (T2D), cancer, and cardiovascular diseases. Therefore, assays for stress related biomarkers could assist in the early diagnosis and could be predictive for disease prognosis. The conventional assay methodologies such as chromatographic and electrophoretic techniques are cumbersome, skill intensive and require expensive instrumentation. Thus, there is sufficient scope to develop a point of care (POC) assay for these biomarkers such that advantages of low cost, fast response time and high sensitivity as well as selectivity can be realized. Carbonyl/Oxidative stress plays a major role in the onset and progression of T2D, and a simple, low cost way of measurement of carbonyl/oxidative stress biomarkers can be beneficial in screening patients for early diagnosis of T2D and its complications thereby assisting current clinical practice. The focus of this thesis was to develop colorimetric assays for monitoring carbonyl/oxidative stress biomarkers associated with T2D. Cationic polythiophene (PT); a water-soluble conjugated polymer was used as a luminescent reporter for the optical detection of these biomarkers. The developed assay consists of two modules; a sample fractioning unit; a filter paper (FUSION 5) for removal of large molecules from clinical samples without requiring external stimuli, and a transduction unit utilizing polyvinylidene fluoride (PVDF) membrane impregnated with (PT) for colorimetric sensing in a flow-through format. The sensing strategy is based on monitoring the changes in optical properties of PT with its associated conformational changes when interacting with a peptide nucleic acid (PNA)/aptamer in the presence and in the absence of target biomarkers. As a proof of concept, the developed assay methodology utilizing PT and PNA/aptamer was validated using different carbonyl/oxidative stress biomarkers such as microRNA (mir21), DNA damage molecule; 8-hydroxy-2′-deoxyguanosine (8-OHdG) and Glyceraldehyde derived Advanced Glycation End Products (Gly-AGEs) without requiring tedious sample pre-treatment and clean up protocols. Colorimetric responses for these biomarkers were obtained at clinically relevant concentrations and could therefore find applications in relation to the management of metabolic diseases such as T2D in a clinical setting as well as in the patient’s home, thus providing attractive and affordable healthcare solutions for field diagnostics.